Amplified Fragment Length Polymorphism-Based Detection of Deoxyribonucleic Acid Methylation and the Analysis Of Three Mads-Box Genes In Oil Palm (Elaeis Guineensis Jacq.) - Au, Adelene Yong Shu Mei (2006)
Tissue culture propagation can induce genetic and epigenetic changes in regenerated plants. In oil palm and other plants, these changes could result in floral and vegetative abnormalities, also termed as ‘somaclonal variations’. DNA methylation is considered to be a potential mechanism by which somaclonal variants experience changes in their gene expression pattern. Most genes controlling the flower architecture is largely determined by homeotic genes containing a conserved MADS-box domain. Compared to Arabidopsis thaliana and Antirrhinum majus, little is known about MADS-box genes controlling flower development in oil palm. To detect the changes in methylation of random genomic sequences in the vicinity of MADS-box genes among the normal, abnormal and reverted oil palm regenerants, a novel DNA fingerprinting technique called MADS-box directed profiling which is an AFLP-based technology is described. The technique involves three steps: (i) digestion of the genomic DNA with methylation-sensitive enzymes and ligation of adapter, (ii) amplification of the selective fragments using a specific primer (MADS5’R) and (iii) gel analysis of the amplified fragments. One-hundred twenty five polymorphisms were identified throughout the study. The 20 most interesting polymorphisms were selected for analysis of which 16 were successfully cloned and sequenced from a total of 126 individual DNA samples sourced from 17 oil palm clones. Most altered methylation especially in the abnormal palms is of the hypo type. Analysis from the cloned polymorphic fragments revealed that they are constantly present in an overlapping manner and therefore could be classified into three groups based on their common consensus. In the latter effort to obtain the full-length DNA sequences, 3’RACE extension was done. Three new full-length MADS-box genes, namely OPMADS14, OPMADS15 and OPMADS16 were identified. The sequence constituting these MADS-box fragments are thought to be novel as they are not found in the oil palm MADSbox collection. They showed similarity to the Arabidopsis thaliana AGL6, FUL and SEP1, respectively. Their genomic organizations related to methylation were studied through Southern analysis. Cytosine methylation polymorphism indeed exists at the CCGG sites of some MADS-box sequence among the oil palm clones. Expression patterns were studied by RT-PCR. OPMADS15 showed no differences in the abundance of transcript level between the normal or mantled palms when compared between similar tissues. Thus, it is concluded that OPMADS15 is a flower-specific MADS-box gene that is involved in flower development and its expression is not affected by the differences in mantling condition, or at least in the oil palm clones used for this study. The fact that OPMADS14 and OPMADS16 transcripts were also found in non-floral organs reflect that these genes may not be necessarily involved in flower development per se but may play wider roles in different aspects of plant development.